FLOW EXPERIENCE DAN ENTREPRENEURIAL SATISFACTION DALAM BISNIS BERKELANJUTAN DI INDONESIA ERA COVID19 - Wilson Alexander; Chrisanty Victoria Layman (Ultima Management : Jurnal Ilmu Manajemen, 2021)
Abstract- Economic difficulties along with the ongoing situation of the COVID-19 pandemic requires start-ups to be innovative in order to stay in the market. As a developing country, the Indonesian government fully supports business development in the country by constantly increasing the number of entrepreneurs and local businesses to act as one of the strong foundations in Indonesia's economy. However, many of these entrepreneurship endeavors does not last and are not sustainable. Therefore, this research aims to evaluate the influence of entrepreneurship, market orientation, and network on business sustainability, flow experience and entrepreneurial satisfaction of Indonesian entrepreneurs. Furthermore, this study was conducted using a quantitative method with a non-probability sampling technique, in which the respondent subjects are 225 entrepreneurs who are currently doing business in Indonesia. Data is then analyzed using structural equation modeling (SEM) with the software SPSS and AMOS. Results from this research indicate that there was a significant influence of entrepreneurship, market orientation, and network toward business sustainability, flow experience and entrepreneurial satisfaction in Indonesian entrepreneurs. In this study, it can be concluded that in establishing business sustainability, an entrepreneur must take several ways to form competence in running his business in the long term found in the flow experience. However, some limitation to the research is that there were limitations to time and interactions that could be performed during the Covid-19 restriction. Keywords: Business Sustainability; Entrepreneurial Satisfaction; Entrepreneurship; Flow Experience; Market Orientation